A comparison of different input devices for a 3D environment - Dang, Nguyen Thong; Tavanti, Monica; Rankin, Ivan; Cooper, Matthew (International journal of industrial ergonomics, 2009)
This paper presents a usability study comparing wand, voice, and two tablet-PC based interfaces across a task requiring three-dimensional surface exploration, information gathering and recall of information. The aim of this study was to identify a suitable interaction interface, among the ones implemented in a three-dimensional environment for Air Traffic Control, for interactive exploration of and gathering information about three-dimensional weather structures. Data concerning time, error rate, number of control actions as well as participants’ feedback on ease of learning, ease of use, frustration and perceived difficulty of the performed task were collected. The results indicate that the wand interface supported better performance when compared with the other interaction interfaces. Among the four interaction interfaces, the voice interface seems to present several limitations, mostly related to time lag in the voice recognition, which was judged by the subjects as a source of frustration.